Covid-19 pandemic and its effect on capital market development: A literature review - Palupi, Agustin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to see how the COVID-19 pandemic can affect the development of the capital market. This is done by reviewing articles through the literature review method. There are as many as 15 articles that will be studied in this study. This research concludes that investor confidence can remain stable or increase despite the COVID-19 pandemic because of good government policies. Although this policy can help the capital market, the capital market will remain uncertain without medical solutions such as vaccines or drugs sold cheaply. Therefore, it is necessary to have good management from the top in dealing with various shocks in the stock market, which can indicate the quality of corporate governance.